Environment‐induced epigenetic reprogramming in genomic regulatory elements in smoking mothers and their children. Issue 3 (24th March 2016) - Bauer, Tobias; Trump, Saskia; Ishaque, Naveed; Thürmann, Loreen; Gu, Lei; Bauer, Mario; Bieg, Matthias; Gu, Zuguang; Weichenhan, Dieter; Mallm, Jan‐Philipp; Röder, Stefan; Herberth, Gunda; et al.
Abstract: Epigenetic mechanisms have emerged as links between prenatal environmental exposure and disease risk later in life. Here, we studied epigenetic changes associated with maternal smoking at base pair resolution by mapping DNA methylation, histone modifications, and transcription in expectant mothers and their newborn children. We found extensive global differential methylation and carefully evaluated these changes to separate environment associated from genotype‐related DNA methylation changes. Differential methylation is enriched in enhancer elements and targets in particular "commuting" enhancers having multiple, regulatory interactions with distal genes. Longitudinal whole‐genome bisulfite sequencing revealed that DNA methylation changes associated with maternal smoking persist over years of life. Particularly in children prenatal environmental exposure leads to chromatin transitions into a hyperactive state. Combined DNA methylation, histone modification, and gene expression analyses indicate that differential methylation in enhancer regions is more often functionally translated than methylation changes in promoters or non‐regulatory elements. Finally, we show that epigenetic deregulation of a commuting enhancer targeting c‐Jun N‐terminal kinase 2 (JNK2) is linked to impaired lung function in early childhood. Synopsis: Genome‐wide epigenomic and transcriptomic data reveal that maternal smoking induces important changes in the methylome of mothers and their children that affect in particular enhancer regions. These changes are stably maintained for years in the epigenome of the child. Comprehensive genome‐wide sequencing reveals global changes in DNA methylation, chromatin states, and gene expression in mothers and their children associated with smoking during pregnancy. Such DNA methylation changes are stably maintained for years in the child. Taking into account genotype effects on methylation reveals a core set of genotype‐independent, environmental driven DMRs, which are massively enriched in enhancers. Epigenetic deregulation of JNK2 enhancer at time of birth is linked to impaired lung function later in children's life. Abstract : Genome‐wide epigenomic and transcriptomic data reveal that maternal smoking induces important changes in the methylome of mothers and their children that affect in particular enhancer regions. These changes are stably maintained for years in the epigenome of the child.